Congenital Cytomegalovirus Infection Manifesting as Neonatal Persistent Pulmonary Hypertension: Report of Two Cases. (31st May 2011) - Walter-Nicolet, Elizabeth; Leblanc, Magali; Leruez-Ville, Marianne; Hubert, Philippe; Mitanchez, Delphine
Abstract : Various neonatal symptoms can lead to a diagnosis of congenital CMV infection. We report two cases of persistent pulmonary hypertension in relation with congenital CMV infection following maternal primary infection and reinfection, respectively. Both infants had severe refractory hypoxemia, requiring high-frequency ventilation, inhaled nitric oxide and inotropic support. One of them required extracorporeal membrane oxygenation for five days. Ganciclovir therapy was attempted in the two cases on day 12 postnatal. One of the infant died on day 15 postnatal. The other survived and is developing uneventfully at 15 months of age. Conclusion : Neonatal persistent pulmonary hypertension can be the consequence of congenital CMV infection. Intensive respiratory support and IV ganciclovir are indicated in case of life-threatening condition.